DOZ047.51: Swallowing and pulmonary diagnoses in children with EA and TEF. (24th June 2019) - Maybee, J; Deck, J; Jensen, E; Ruiz, A; Corbett, B; Deterding, R; Friedlander, J; Helland, S; Soden, J; Wine, T; Prager, J; DeBoer, E
Abstract: Introduction: Children with repaired congenital esophageal atresia/tracheoesophageal fistula (EA/TEF) are at high risk of aerodigestive morbidity. We hypothesized that age and coexisting pulmonary diagnoses are associated with dysphagia in this population. Methods: Retrospective review of children with EA/TEF seen in the aerodigestive program between 2011 and 2015 was carried out and comorbidities, video fluoroscopic swallow studies (VFSS), chest CT, and bronchoscopy results were reviewed. VFSS was considered abnormal if there was aspiration, deep laryngeal penetration, significant residue, or delayed initiation. Mann–Whitney U test was used to examine VFSS results by age. Fisher's exact test was used to assess the relationship between VFSS result and comorbidities. Results: Ninety VFSS were performed on 44 children with EA/TEF (median 2 studies per patient, range: 0–7). Fifty three percent (23/39) children had at least one abnormal VFSS. Seventeen children had VFSS change between normal and abnormal over time, with 11 normal on their most recent VFSS. Younger children (Mdn = 1.57 years) were more likely to have an abnormal test result than older children (Mdn = 3.55 years) ( p = 0.001). Children with severe tracheomalacia (>90% tracheal collapse visualized on flexible bronchoscopy) had a higher incidence of abnormal VFSS (14/20; 70%) than the other children with EA/TEF (9/24; 38%) ( P = 0.04). Children with other pulmonary and airway comorbidities, including gestation age <36 weeks ( P = 0.24), vocal fold immobility ( P = 0.1), abnormal chest CT ( P = 0.1), tended to have an increased incidence of abnormal VFSS but did not reach statistical significance in this cohort. Discussion: Dysphagia was prevalent in this cohort and related to age and severe tracheomalacia. This reinforces the need for a multidisciplinary evaluation including feeding and swallowing evaluation. In this rare disease, we must collaborate between sites to improve our understanding of aerodigestive diagnoses and disease outcomes.